Less Urinary Tract Infection by Earlier Removal of Bladder Catheter in Surgical Patients Receiving Thoracic Epidural Analgesia. Issue 6 (1st October 2009) - Zaouter, Cedrick; Kaneva, Pepa; Carli, Franco
Abstract : Background and Objectives: It is common practice to catheterize the bladder in the presence of epidural analgesia and to leave the bladder catheter in situ to avoid postoperative urinary retention. However, bladder catheterization carries the risk for urinary tract infection (UTI). The objective of this randomized control trial was to assess whether the incidence of UTI will differ among patients receiving standard care and patients who have the bladder catheterization discontinued on the morning after surgery with the epidural still functioning. Methods: Patients at low risk for postoperative urinary retention, scheduled for thoracic and abdominal surgery and receiving continuous thoracic epidural analgesia, were randomized on the morning after surgery to 2 groups: in the early removal group (n = 105), the bladder catheter was removed on the same morning after surgery, whereas in the standard group (SG) (n = 110), the bladder catheter was removed when epidural analgesia was discontinued (3-5 days). Urinary bladder volume was assessed by ultrasound. Primary and secondary outcomes were the incidence of UTI and rate of recatheterization. Results: Two hundred fifteen patients were randomized. There were 17 UTI cases in total, with 15 (14%) in the SG and 2 (2%) in the early removal group ( P = 0.004). The incidence of recatheterizations was not different between the 2 groups ( P = 0.09) and did not correlate with the site of epidural insertion. When matched for the types of surgery, the duration of hospital stay was longer in the patients who contracted UTI ( P = 0.004). There were more patients older than 65 years in the SG. Conclusions: Leaving the bladder catheter as long as the epidural analgesia is maintained results in a higher incidence of UTI and prolonged hospital stay. Removal of the bladder catheter on the morning after surgery does not lead to higher rate of catheterizations.